INSTRUMEN PENILAIAN FORMATIF BERBASIS HOTS PENGUKUR KEMAMPUAN BERPIKIR KRITIS SISWA SMA (POKOK BAHASAN TEORI KINETIK GAS) - Alvianty Noer Cahya; Albertus Djoko Lesmono; Maryani Maryani (JURNAL PEMBELAJARAN FISIKA, 2022)
This study aims to determine the validity of the HOTS assessment instrument, the reliability of the HOTS assessment instrument from the test instrument. The test was carried out in class XII MIPA 7 and XII MIPA 8 at SMA Negeri 2 Jember in the even semester. The instrument used in this research is in the form of 20 essay questions on the kinetic theory of gases. This research is a descriptive study using a quantitative approach through ADDIE modeling. The results showed that the average value of the level of validity was 91.11% and the value of the degree of reliability coefficient r11 was 0.9156. The results showed that the results of the analysis of the level of difficulty of the items contained 14 items that were feasible or acceptable and 6 items that were not feasible because they had a level of difficulty that was not in accordance with the criteria for the level of difficulty of the items that were good and the results of the analysis of the distinguishing power of the items, where The results of the analysis show that there are 12 items that are suitable for use with some improvement of questions and 8 items that are not suitable to be used because they have distinguishing power in the bad category or do not match the criteria for good discriminating power. The results showed that students' critical thinking skills in solving physics problems on gas kinetic theory material as measured using the higher order thinking skill (HOTS) test instrument could be categorized as moderate.